Pemulihan Ekonomi Melalui Pembangunan Kebun Bibit Desa Menggunakan Metode Participatory Action Research (PAR) - Afni z; Fara Merian Sari; Prihati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
During the Covid-19 pandemic, policies are needed in order to help economic recovery for society. This service opens public access to the policy of developing Village Seed Gardens (KBD), as an alternative to economic and environmental improvements. By using the Participatory Action Research (PAR) method with the main pillars of research, action, and participation. Partners involved in this program are seven villages in Lubuk Dalam District, Siak Regency, Riau. The results achieved were the form of community accessibility to government policies, community involvement in transformative activities to improve the economy and environment, which were obtained through assisting the development of KBD in seven villages that could independently produce thousands of seedlings for the surrounding community. Apart from economic recovery as a short-term benefit, also has long-term benefits for environmental restoration by changing degraded land to be more productive.